Corrosion test method for seabed cement-based material
By configuring artificial seabed silt and conducting microscopic analysis, the high cost and uncertainty of seabed silt corrosion simulation have been solved, enabling precise control of erosion factor concentrations, improving research efficiency and safety, and providing durability assessments for marine engineering.
Patent Information
- Application Number
- CN202511578003.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-09
AI Technical Summary
Existing technologies cannot effectively simulate the corrosion of cement-based materials by seabed silt, resulting in high costs, low repeatability, and operational risks. Furthermore, it is difficult to accurately control the concentration of erosion factors, thus failing to meet long-term monitoring needs.
By configuring artificial seabed silt and conducting water content and shear strength tests to simulate the seabed environment, and using XRD and SEM for microscopic analysis, the concentration of key erosion factors is controlled to simulate the erosion characteristics of different marine environments, thus avoiding the heterogeneity and instability of natural silt.
It enables precise control of erosion factor concentration, reduces testing costs, improves research efficiency, ensures operational safety, provides a basis for forward-looking engineering design, and is suitable for durability assessment of marine engineering projects.
Smart Images

Figure CN121298566A_ABST
Abstract
Description
Technical Field
[0001] This invention pertains to seabed corrosion testing methods, specifically a corrosion testing method for seabed cement-based materials. Background Technology
[0002] The corrosion of cement-based materials by sulfate ions and the corrosion of steel reinforcement by chloride ions are important reasons for the deterioration of the performance of cement-based materials, the degradation of the durability of engineering structures, and the shortening of service life in marine engineering. Therefore, it is particularly important to investigate the actual situation of seabed silt corrosion of cement-based materials in the marine environment. However, in reality, natural seabed silt has many limitations, such as extremely high collection costs, significant natural differences, and poor experimental repeatability. At present, there is no specific test method for the corrosion of cement-based materials by seabed silt, which cannot meet different research objectives. In-situ monitoring (directly monitoring the performance of cement-based materials on the seabed) is the best method, but the requirements for equipment in the seabed environment are far greater than those on land: the equipment's weather resistance is insufficient; the high pressure on the seabed (such as 100MPa in the deep sea), low temperature, and biological attachment (such as shellfish and algae covering sensors) can cause monitoring equipment (such as compressive strength sensors and chloride ion permeation sensors) to fail. Signal transmission is challenging: There are no wireless signals on the seabed, requiring data transmission via cables. However, these cables are easily washed away by ocean currents and snagged by fishing nets, and laying cables in deep-sea areas is extremely expensive (up to hundreds of thousands of yuan per kilometer). If wireless transmission (such as acoustic signals) is used, signal attenuation is rapid, and the transmission distance is limited (only a few hundred meters), failing to meet the needs of large-scale monitoring. Long-term power supply is also difficult: In-situ monitoring requires continuous power. Current technologies mostly rely on batteries (with a lifespan of only 3-6 months) or seabed nuclear power plants (extremely expensive), which cannot support long-term monitoring for several years. Field testing is costly and maintenance is difficult: Long-term testing (e.g., 3 years) requires continuous monitoring of sediment composition, microbial activity, and environmental parameters, necessitating dedicated personnel for maintenance. Furthermore, the equipment wear and tear rate is high (e.g., sensor aging), making it difficult for most laboratories to afford.
[0003] The erosion of concrete by seabed silt is the result of the synergistic effects of multiple factors, including salt, sulfate, chloride ions, microorganisms, and organic matter. Natural seabed silt exhibits significant compositional variations due to differences in sea area and depth, making it difficult to precisely match experimental targets. Natural seabed silt suffers from two major drawbacks: 1) Inhomogeneous composition: silt from different locations within the same sea area may differ in salt and organic matter content by more than 20%, leading to large fluctuations in the composition of silt used in the same batch of experiments; 2) Unstable state: natural silt is prone to microbial degradation and salt leaching after collection, resulting in variations in erosion intensity during the experiment. Summary of the Invention
[0004] Purpose of the invention: In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a convenient and flexible corrosion testing method for seabed cement-based materials.
[0005] Technical solution: The corrosion testing method for seabed cement-based materials according to the present invention includes the following steps:
[0006] Step 1: Prepare artificial seabed silt;
[0007] Step two: Conduct water content and shear strength tests on the artificial seabed silt;
[0008] Step 3: Plot the shear stress-shear rate curve of the artificial seabed silt to determine the yield stress and plastic viscosity of the artificial seabed silt.
[0009] Step 4: Completely bury cement-based materials with different proportions in artificial seabed silt, cover with a sealing device, place them in a constant temperature and humidity chamber or environmental test chamber, set the temperature and humidity parameters, start the immersion test, and replenish the evaporated water and consumed salt.
[0010] Step 5: Take out the cement-based material at predetermined time intervals for observation and testing to obtain the erosion law of the cement-based material in the artificially prepared seabed silt environment and determine the construction mix ratio.
[0011] Furthermore, in step one, the artificial seabed silt includes kaolin, sodium sulfate, sodium chloride, water, quartz sand, magnesium sulfate, sugar, and amino acid monomers.
[0012] Further, in step two, the water content test of the artificial seabed silt includes the following steps: take a clean tin foil bowl, weigh it and record its mass; use a dried spoon to take the artificial seabed silt sample and put it into the tin foil bowl, weigh the total mass of the artificial seabed silt sample and the tin foil bowl; dry the tin foil bowl at 105~110℃; take out the tin foil bowl, dry and cool it to room temperature and then weigh it; repeat until the difference between two weighings does not exceed 0.002g, and record the final mass.
[0013] Furthermore, in step two, the formula for calculating the water content of the artificial seabed sediment is:
[0014] Where w is the water content of the artificial seabed silt, m1 is the mass of the foil bowl, m2 is the total mass of the artificial seabed silt sample and the foil bowl, and m3 is the final mass.
[0015] Furthermore, in step two, the shear strength is measured by a rheometer to obtain the shear stress of the artificial seabed silt under different constant shear rates and the shear strength under periodically varying shear stress or strain.
[0016] Furthermore, in step four, the cement-based material is a cement-based material that has been cured for more than 28 days.
[0017] Further, in step four, the cement-based material includes the following components by weight: 370 parts cement, 31-93 parts fly ash, 31-93 parts mineral powder, 707 parts sand, 1106 parts crushed stone, 153 parts water, and 7.41 parts polycarboxylate superplasticizer.
[0018] Furthermore, in step four, the temperature is 18~22℃ and the humidity is 65~70%.
[0019] Furthermore, in step four, the spacing between cement-based materials with different proportions is greater than half the side length of the cement-based material.
[0020] Furthermore, in step five, observations and tests are obtained through XRD and SEM.
[0021] Test Principle: When X-rays irradiate a crystalline material, the following process occurs: X-rays penetrate the interior of the cement-based material and reach the atomic planes (crystal planes) of different crystals. Atoms on the crystal planes scatter the X-rays, and the scattered waves interfere with each other. When the optical path difference of the scattered waves meets a specific condition (i.e., Bragg's equation: 2d·sinθ = nλ), enhanced interference occurs, forming "diffraction peaks" that can be captured by a detector. This can detect whether deterioration products (such as ettringite and gypsum) are generated, aiding in the analysis of the causes of alkali-aggregate reaction, sulfate corrosion, and other defects.
[0022] SEM, or Scanning Electron Microscope, operates on a workflow revolving around the transformation from electron beam to signal to image: Electron beam emission and focusing: A high-energy electron beam is emitted by an electron gun and focused by an electromagnetic lens into an extremely fine "electron probe" (with a diameter as small as nanometers). Point-by-point scanning of the sample surface: The focused electron beam scans the sample surface point by point and line by line along a pre-defined path, interacting with the surface atoms of the sample. Characteristic signal excitation: When the electron beam interacts with the sample, it excites various signals, among which the core signals used for morphology analysis are secondary electrons (reflecting the unevenness of the sample surface) and backscattered electrons (taking into account both morphology and compositional differences). Signal collection and imaging: A detector collects these characteristic signals, and the signal intensity changes with the morphology / composition of the sample surface; subsequently, the signal intensity is converted into bright and dark pixels in the image, synchronously corresponding to the scanning position of the electron beam, ultimately forming a microscopic morphology image consistent with the sample surface.
[0023] In simple terms, SEM is equivalent to using an "electron beam" instead of "light" to "observe" a sample, and then converting the invisible electronic signals into visible images, thereby breaking through the resolution limitations of optical microscopes (reaching the nanometer level).
[0024] In durability studies, the microscopic changes of materials after being subjected to corrosion such as sulfates are observed, such as the appearance of microcracks and the formation of degradation products (such as gypsum crystals), in order to pinpoint the source of degradation.
[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0026] 1. By adjusting the composition as needed, the concentration of key erosion factors can be precisely controlled, such as chloride ion content of 0.5%~3% and sulfate content of 0.1%~0.8%, which can simulate the erosion characteristics of specific marine environments such as tidal flats, deep sea, and salt marshes;
[0027] 2. Erosion factors can be introduced individually or in combination. For example, only chloride ion penetration can be studied, or sulfate can be added simultaneously to clarify the erosion mechanism of single / composite factors on concrete and avoid interference from unknown impurities in natural silt with the test results.
[0028] 3. Artificial formulation can solve the problem of "uneven composition and unstable state of natural seabed silt" through standardized formulas;
[0029] 4. Artificial seabed silt can significantly optimize the experimental process, reduce collection costs, eliminate the need for offshore operations, save on ship, equipment, and manpower costs, and also eliminate the need to deal with collection permit restrictions in different sea areas;
[0030] 5. The process of concrete erosion can be accelerated by concentrating erosion factors (such as increasing the chloride ion concentration to 2 to 3 times that of natural silt). The natural exposure test that originally required 6 months can be shortened to 1 to 2 months by artificial simulation, which greatly improves the efficiency of research.
[0031] 6. Natural silt may contain heavy metals and harmful microorganisms, such as sulfate-reducing bacteria and pathogenic bacteria. Artificially prepared silt uses only known safe raw materials to avoid exposure of test personnel to unknown pollutants, reduce operational risks, and improve operational safety.
[0032] 7. It can simulate extreme erosion scenarios and assess the durability of concrete under harsh conditions in the future, providing a forward-looking basis for engineering design. Attached Figure Description
[0033] Figure 1 This is a diagram of the apparatus of the present invention;
[0034] Figure 2 This is a flowchart of the preparation process of the present invention;
[0035] Figure 3 This is a graph showing the variation of static shear stress in this invention. Detailed Implementation
[0036] Unless otherwise specified, all materials and reagents used in the following embodiments are commercially available. Experimental methods not specifically described in the embodiments are generally performed under standard conditions or as recommended by the manufacturer. The simulated seabed silt in the following embodiments is from the seabed at a depth of approximately 3.0m below the surface of the original seawater outside the western passage of Shenzhen Bay. Samples were taken directly after the top 1m of silt was excavated at low tide. The soil was homogeneous and virtually devoid of shells. The seabed silt is mainly composed of secondary clay minerals, with the main components being SiO2, Fe2O3, Al2O3, CaO, MgO, K2O, and Na2O.
[0037] Table 1 Basic physical properties of actual seabed silt
[0038]
[0039] like Figure 1 Cement-based material is embedded in artificial seabed silt inside a sealed container 1. A hole is made in the side wall of the sealed container 1 to allow water pipe 2 to pass through. A throttling valve 3 is installed on the water pipe 2. One end of the water pipe 2 is connected to a solution tank 4, which contains a salt solution 5.
[0040] like Figure 2 A corrosion testing method for seabed cement-based materials includes the following steps:
[0041] Table 2. Composition of Artificially Prepared Seabed Silt
[0042]
[0043] Step 1: Prepare artificial seabed silt. Based on the seabed silt formula, the components with the greatest impact on the corrosion of cement-based materials are sulfate ions and chloride ions. In order to simulate the characteristics of high water content and low yield stress of seabed silt, the formula composition of artificially prepared seabed silt is shown in Table 2.
[0044] Step two involves testing the water content and shear strength of the artificial seabed silt.
[0045] (a) Moisture content test:
[0046] (1) Take a clean tin foil bowl, weigh it and record its mass as m1=1g;
[0047] (2) Use the dried spoon to take an appropriate amount of silt sample and put it into the foil bowl. Weigh the total mass of the sample and the foil bowl and record it as m2=101g;
[0048] (3) Place the foil bowl in an oven and dry it at 110°C for 5 hours;
[0049] Take out the tin foil bowl, place it in a desiccator, cool it to room temperature and then weigh it. Repeat the steps of drying, cooling and weighing until the mass difference between two weighings does not exceed 0.002 g, and record the final mass m3 = 61 g.
[0050] The calculation formula for the water content of artificial seabed sludge is:
[0051]
[0052] (2) Test of shear strength: Use an existing rheometer on the market for testing.
[0053] (1) Sample preparation: After collecting the artificially prepared seabed sludge sample, the test should be carried out as soon as possible. If the test cannot be carried out in time, it needs to be properly stored (such as refrigerated storage) to avoid changes in the properties of the sample. Stir the artificially prepared seabed sludge sample evenly to remove possible impurities (such as stones, etc.) to ensure the uniformity and representativeness of the sample. According to the requirements of the rheometer measurement system, take 50 g of sludge sample to fill the working gap of the measurement system and ensure full contact between the sample and the measurement components.
[0054] (2) Instrument calibration and installation: Before using the rheometer, it needs to be calibrated according to the instrument operation manual to ensure the accuracy of measurement parameters such as torque and rotational speed. Select a suitable measurement system. For example, the parallel plate measurement system is suitable for low-viscosity sludge, and the cone plate measurement system requires less sample volume and can provide a more uniform shear field, and install it correctly on the rheometer. Carefully place the prepared sludge sample in the measurement system, adjust the position of the measurement components to make them closely fit with the sample, and avoid the existence of air bubbles or voids.
[0055] (3) Test parameter setting and measurement: According to the properties of the sludge and the test purpose, set appropriate test parameters. The shear rate ranges from 0.01 s -1 to 100 s -1 , and the test is generally carried out at room temperature. However, if the effect of temperature on the shear strength of the sludge needs to be studied, a specific temperature can be set, etc. Start the rheometer and measure the sludge sample according to the preset parameters. The instrument automatically records the changes of data such as torque and rotational speed over time during the shear process. Different test modes can be adopted, such as steady-state shear test to obtain the shear stress of the sludge at different constant shear rates; dynamic shear test, by applying periodically varying shear stress or strain, to study the viscoelastic properties of the sludge and then analyze its shear strength.
[0056] Step 3, after the measurement is completed, use the data processing software supporting the rheometer to process the collected data, and obtain the maximum static shear stress of 47.96 Pa, as Figure 3Torque data was converted into shear stress, and rotational speed data into shear rate, and a shear stress-shear rate curve was plotted. Based on the curve characteristics, parameters such as the yield stress (the minimum shear stress that causes the silt to begin flowing, which can be considered as the initial shear strength of the silt) and plastic viscosity were determined. For example, the shear stress corresponding to when the curve begins to deviate from the linear relationship in the shear stress-shear rate curve is the yield stress. Through the above testing and step-by-step verification, artificially prepared seabed silt with high water content and low yield stress was obtained.
[0057] Step four involves completely burying cement-based materials with different proportions after 28 days of curing in artificial seabed silt. A sealed container is then placed in a constant temperature and humidity chamber or environmental test chamber to simulate the erosion experienced by cement-based materials in contact with seabed silt under sea conditions. Temperature and humidity parameters are set, and the immersion test begins, replenishing evaporated water and consumed salt. A silt height scale is marked on the outside of a transparent container after placing the test blocks and silt. Evaporated water and salt are then replenished by preparing a solution with a concentration equal to the water and salt content of the artificial silt.
[0058] (a) Preparation of materials and equipment
[0059] (1) Preparation of cement-based material specimens: According to the experimental requirements, cement-based materials such as ordinary concrete and cement mortar were prepared according to the standard mix proportions. The mixed materials were poured into the corresponding molds (100mm×100mm×100mm cube molds were used for concrete specimens, and 40mm×40mm×160mm prism molds were used for mortar specimens), and after compaction, the surface was smoothed with a trowel. The strength grade of the cement-based material was C50. The experimental mix proportions and the compressive strength data of the concrete after 360 days of erosion are shown in Table 3. Strength loss rate = (F 28d -F 360d ) / F 28d .
[0060] Table 3. Composition and properties of cement-based materials prepared with different mix proportions
[0061]
[0062] (2) Specimen curing: Place the mold in a standard curing room with a temperature of 20℃ and a relative humidity of 95%. For concrete specimens, demold one day after pouring and continue standard curing until the specified age of 28 days; for mortar specimens, demold after 24 hours and then perform standard curing.
[0063] (3) Prepare a sufficient number of apparatuses, which must be corrosion-resistant and well-sealed to ensure that the solution does not leak or evaporate. Equip with an electronic balance of appropriate accuracy for weighing the specimens; vernier calipers for measuring the specimen dimensions; and other auxiliary tools such as brushes and absorbent towels. Prepare a constant temperature and humidity chamber or environmental test chamber to control the temperature and humidity of the immersion environment (generally, the temperature is controlled at 20℃ and the humidity is kept at a natural level).
[0064] (II) Immersion Test Procedure
[0065] (1) Pretreatment of specimens
[0066] Remove the cured cement-based material specimens from the curing room, clean the surface impurities with a brush, and dry the surface with an absorbent towel. Use vernier calipers to measure the dimensions of the specimens at different locations (for cubic specimens, measure the length of three edges; for prism specimens, measure the length, width, and height), and record the initial dimensional data. Use an electronic balance to weigh the initial mass of the specimens, accurate to 0.01g.
[0067] (2) Fully embedded specimen
[0068] Place the treated specimens into the apparatus, ensuring a 20mm gap between them (generally no less than half the side length of the specimen) to prevent contact and ensure effective erosion. Slowly pour artificially prepared seabed silt into the apparatus, completely submerging the specimens. The silt layer should be 50mm higher than the top of the specimens. Seal the apparatus and place it in a constant temperature and humidity chamber or environmental test chamber. Set the temperature and humidity parameters and begin the immersion test.
[0069] Step 5: Take out the cement-based material at predetermined time intervals for observation and testing to obtain the erosion law of the cement-based material in the artificially prepared seabed silt environment and determine the construction mix ratio.
[0070] During the soaking process, the specimens were taken out for observation and testing at predetermined time intervals (0d, 30d, 60d, 90d, 120d, 180d, 270d, 360d).
[0071] After each specimen is removed, rinse the surface with clean water to remove the solution, and dry it with an absorbent towel. Observe whether there are any corrosion phenomena such as cracks, peeling, or swelling on the surface of the specimen, and record the corrosion characteristics.
[0072] The dimensions and mass of the specimen were measured again, and compared with the initial data to calculate the rate of change of dimensions and the rate of change of mass. The rate of change of dimensions = (measured dimension - initial dimension) / initial dimension × 100%; the rate of change of mass = (measured mass - initial mass) / initial mass × 100%.
[0073] The eroded specimens can also undergo relevant pretreatment for microscopic analysis before being subjected to microscopic tests such as XRD and SEM, thereby enabling corresponding microscopic data analysis.
[0074] The erosion patterns of cement-based materials in artificially prepared seabed silt environments were finally obtained, and these patterns were applied to practical engineering projects to guide concrete mix design and corrosion resistance design in subsea engineering construction.
[0075] Because marine engineering concrete incorporates high-quality mineral powder and fly ash, has a high content of cementitious materials, and uses high-efficiency water-reducing agents, the concrete is quite viscous and its pumpability is not ideal. Experimental data also shows that the higher the mineral powder content, the higher the early strength of the concrete, but the more prone it is to cracking. The strength loss rate gradually decreases from top to bottom, but with excessive addition of mineral powder, the decrease in strength loss rate is not significant. Therefore, for the design of high-performance concrete for tower columns in marine engineering, the amount of mineral powder should be appropriately increased. Considering both economic efficiency and erosion resistance, we adopted the second mix design.
Claims
1. A corrosion testing method for seabed cement-based materials, characterized in that, Includes the following steps: Step 1: Prepare artificial seabed silt; Step two: Conduct water content and shear strength tests on the artificial seabed silt; Step 3: Plot the shear stress-shear rate curve of the artificial seabed silt to determine the yield stress and plastic viscosity of the artificial seabed silt. Step 4: Completely bury cement-based materials with different proportions in artificial seabed silt, cover with a sealing device, place them in a constant temperature and humidity chamber or environmental test chamber, set the temperature and humidity parameters, start the immersion test, and replenish the evaporated water and consumed salt. Step 5: Take out the cement-based material at predetermined time intervals for observation and testing to obtain the erosion law of the cement-based material in the artificially prepared seabed silt environment and determine the construction mix ratio.
2. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step one, the artificial seabed silt includes kaolin, sodium sulfate, sodium chloride, water, quartz sand, magnesium sulfate, sugar, and amino acid monomers.
3. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step two, the water content test of the artificial seabed silt includes the following steps: take a clean tin foil bowl, weigh it and record its mass; use a dried spoon to take the artificial seabed silt sample and put it into the tin foil bowl, weigh the total mass of the artificial seabed silt sample and the tin foil bowl; dry the tin foil bowl at 105~110℃; take out the tin foil bowl, dry and cool it to room temperature and then weigh it; repeat until the difference between two weighings does not exceed 0.002g, and record the final mass.
4. The corrosion testing method for seabed cement-based materials according to claim 3, characterized in that: In step two, the formula for calculating the water content of the artificial seabed silt is as follows: Where w is the water content of the artificial seabed silt, m1 is the mass of the foil bowl, m2 is the total mass of the artificial seabed silt sample and the foil bowl, and m3 is the final mass.
5. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step two, the shear strength is measured by a rheometer to obtain the shear stress of the artificial seabed silt under different constant shear rates and the shear strength under periodically varying shear stress or strain.
6. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step four, the cement-based material is a cement-based material that has been cured for more than 28 days.
7. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step four, the cement-based material includes the following components by weight: 370 parts cement, 31-93 parts fly ash, 31-93 parts mineral powder, 707 parts sand, 1106 parts crushed stone, 153 parts water, and 7.41 parts polycarboxylate superplasticizer.
8. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step four, the temperature is 18~22℃ and the humidity is 65~70%.
9. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step four, the interval between cement-based materials with different proportions is greater than half the side length of the cement-based material.
10. The corrosion testing method for seabed cement-based materials according to claim 1, characterized in that: In step five, observations and tests are obtained through XRD and SEM.